Tetraoxygenated xanthones from the latex of Garcinia cowa growing in Viet Nam - Nguyen Thi Kim An,; Dinh Thi Ha ,; Pham Quoc Long,; Tran Thi Thu Thuy , (Vietnam Journal of Science and Technology, 2018)
Seven tetraoxygenated xanthones, namely fuscaxanthone A,7-O-methylgarcinone E, cowagarcinone A, cowaxanthone, rubraxanthone, cowanin and cowanol, were isolated from the dichloromethane extract of the latex of Garcinia cowa_Roxb. ex Choisy. Their structures were elucidated on the basis of 1D, 2D NMR spectroscopic data and comparison with reported data.